2016
DOI: 10.1038/srep34726
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid boron nitride-natural fiber composites for enhanced thermal conductivity

Abstract: Thermal conductivity was dramatically increased after adding natural fiber into hexagonal boron nitride (hBN)/epoxy composites. Although natural fiber does not show high-thermal conductivity itself, this study found that the synergy of natural fiber with hBN could significantly improve thermal conductivity, compared with that solely using hBN. A design of mixtures approach using constant fibers with increasing volume fractions of hBN was examined and compared. The thermal conductivity of the composite containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 40 publications
1
30
0
Order By: Relevance
“…They concluded that the BN added composite shows better “K” and smaller D k value compared with AlN reinforced composite, and proposed optimum values for HGM with BN were presented. Natural fiber strengthened epoxy composites are the poor thermal conductors; C. Xia et al added various percentages of h‐BN with natural fibre epoxy composites and evaluated the “K” of pure and filler added composites, and the values were reported. Maximum “K” value was 6.418 W m −1 K −1 corresponding to 43.8% filler incorporation.…”
Section: Role and Effect Of Filler/hybrid Filler Addition On Thermal mentioning
confidence: 99%
“…They concluded that the BN added composite shows better “K” and smaller D k value compared with AlN reinforced composite, and proposed optimum values for HGM with BN were presented. Natural fiber strengthened epoxy composites are the poor thermal conductors; C. Xia et al added various percentages of h‐BN with natural fibre epoxy composites and evaluated the “K” of pure and filler added composites, and the values were reported. Maximum “K” value was 6.418 W m −1 K −1 corresponding to 43.8% filler incorporation.…”
Section: Role and Effect Of Filler/hybrid Filler Addition On Thermal mentioning
confidence: 99%
“…Xia and co‐works demonstrated as well the synergistic effect between the natural fiber (kenaf) and h‐BN in epoxy. This type of fiber is not conductive by itself, however the thermal conductivity of composite obtained from h‐BN/kenaf fiber/epoxy with 43.6 wt % of h‐BN was 72.3% higher than only kenaf/epoxy.…”
Section: Resultsmentioning
confidence: 90%
“…The flax/basalt hybrid reinforced with vinyl ester laminates enhances the durability and water repellence behaviour [11]. The inclusion of kenaf fibre with hexagonal boron nitride (hBN) and epoxy increases the thermal conductivity of the composite than with hBN and epoxy alone [12].…”
Section: Introductionmentioning
confidence: 99%